Gonotrophic cycle and survivorship of Culex quinquefasciatus (Diptera: Culicidae) using sticky ovitraps in Monterrey, northeastern Mexico - Elizondo Quiroga, Armando Erick; Flores Suárez, Adriana Elizabeth; Elizondo Quiroga, Darwin; Ponce García, Gustavo; Blitvich, Bradley J.; Contreras Cordero, Juan Francisco; González Rojas, José Ignacio; Mercado Hernández, Roberto; Beaty, Barry J.; Fernández Salas, Ildefonso (2006)
Mark–release–recapture experiments were conducted to determine the length of the gonotrophic cycle and rate of survivorship of Culex quinquefasciatus Say in Monterrey, northeastern Mexico. A total of 2,352 field-caught Cx. quinquefasciatus females were marked and released at 8–12 h postemergence in 2 field trials. Sticky ovitraps were used to recapture marked gravid females. One hundred and ten (4.6%) marked females were recaptured during a 12-day sampling period. Recapture rates for the 2 individual trials were 6.4% and 3.5%. The length of the gonotrophic cycle, calculated as the average time between the initial blood meal and the time of recapture of gravid females, was 2–3 days. The first blood-fed mosquitoes were recaptured on the 2nd day postrelease. Gravid egg-laying females were most commonly recaptured at 2–3 days postfeeding. Daily survival estimates for the 2 release dates were of 0.871 and 0.883, respectively.